Phosphorus removal from water with an iron functionalised biochar produced from sunflower seed husks: A circular economy-based solution for the agro sector - Sanja Cojbasic; Sabolc Pap; Jelena Prodanovic; John Milan van der Bergh; Stuart W. Gibb; Ulrike Gayh; Maja Turk Sekulic (Biomass and Bioenergy, 2026)

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Removal of Copper and Lead Ions from Water Using Dopamine-Modified Waste Marine Plastic - Huiyi Zhang; Stuart W. Gibb; Neil A. James; Kenneth G. Boyd; Sabolc Pap (Environmental Processes, 2025)

Sustainable remediation of macrolide antibiotic from water using a novel Fe oxide/biochar nanocomposite: Adsorption behaviour and mechanistic analysis - Sabolc Pap; Lisa Shearer; Stuart W. Gibb (Journal of Environmental Chemical Engineering, 2025)

Co-developing frameworks towards environmentally directed pharmaceutical prescribing in Scotland – A mixed methods study - Lydia Niemi; Naoko Arakawa; Miriam Glendell; Zisis Gagkas; Stuart Gibb; Claire Anderson; Sharon Pfleger (Science of The Total Environment, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Lanthanum and cerium functionalised forestry waste biochar for phosphate removal: Mechanisms and real-world applications - Sabolc Pap; Qunying Zhao; Ilgaz Cakin; Paul P.J. Gaffney; Stuart W. Gibb; Mark A. Taggart (Chemical Engineering Journal, 2024)

Comparison of two carbonaceous supported Fe-rich adsorbents for arsenate removal: A functionalisation and mechanistic study with applicability to groundwater treatment - Sabolc Pap; Maja Turk Sekulic; Hai Nguyen Tran; Huan-Ping Chao; Peter J. Gilbert; Stuart W. Gibb; Mark A. Taggart (Chemosphere, 2024)

Effective removal of metformin from water using an iron-biochar composite: Mechanistic studies and performance optimisation - Sabolc Pap; Lisa Shearer; Stuart W. Gibb (Journal of Environmental Chemical Engineering, 2023)

Pilot-scale phosphate recovery from wastewater to create a fertiliser product: An integrated assessment of adsorbent performance and quality - Sabolc Pap; Huiyi Zhang; Aleksandra Bogdan; Derek T. Elsby; Stuart W. Gibb; Barbara Bremner; Mark A. Taggart (Water Research, 2023)

Evaluating wipe sampling parameters to assess method performance and data confidence during remediation of hazardous pesticide misuse chemicals on indoor materials - Stuart A. Willison; Daniel Stout; Amy Mysz; James Starr; Dennis Tabor; Barbara Wyrzykowska-Ceradini; Josh Nardin; Eric Morris; Emily Gibb Snyder (Science of The Total Environment, 2023)

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Synthesis optimisation and characterisation of chitosan-calcite adsorbent from fishery-food waste for phosphorus removal - Sabolc Pap; Caroline Kirk; Barbara Bremner; Maja Turk Sekulic; Stuart W. Gibb; Snezana Maletic; Mark A. Taggart (Environmental Science and Pollution Research, 2020)
Here, Box-Behnken design (BBD) approaches were utilised to optimise synthesis methodology for the chitosan-calcite rich adsorbent (CCM) made from fishery-food waste material (crab carapace), using low-temperature activation and potassium hydroxide (KOH). The effect of activation temperature, activation time and impregnation ratio was studied. The final adsorbent material was evaluated for its phosphorus (P) removal efficiency from liquid phase. Results showed that impregnation ratio was the most significant individual factor as this acted to increase surface deacetylation of the chitin (to chitosan) and increased the number of amine groups (–NH 2 ) in the chitosan chain. P removal efficiency approached 75.89% (at initial P concentration of 20 mg/L) under optimised experimental conditions, i.e. where the impregnation ratio for KOH:carapace (g/g) was 1:1, the activation temperature was 105 °C and the activation time was 150 min. Predicted responses were in good agreement with the experimental data. Additionally, the pristine and CCM material were further analysed using scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX), Brunauer-Emmett-Teller technique (BET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis (TGA). Characterisation showed enhancements in surface chemistry (introducing positively charged amine groups), textural properties and thermal stability of the CCM.

Introduction of human pharmaceuticals from wastewater treatment plants into the aquatic environment: a rural perspective - Carolina Nebot; Raquel Falcon; Kenneth G. Boyd; Stuart W. Gibb (Environmental Science and Pollution Research, 2015)

Photoacclimation in the marine diatom Skeletonema costatum - Tracy Anning; Hugh L. MacIntyre; Sandra M. Pratt; Pippa J. Sammes; Stuart Gibb; Richard J. Geider (Limnology and Oceanography, 2000)
Photoacclimation was examined in the marine diatom Skeletonema costatum, which was subjected to reciprocal shifts between irradiances of 50 (low‐light) and 1,200 (high‐light) µmol photons m −2 s −1 . Cell chlorophyll a and fucoxanthin contents were higher but diadinoxanthin and diatoxanthin contents lower in cells grown at 50 µmol photons m −2 s −1 than in cells shifted to 1200 µmol photons m −2 s −1 . Cell carbon contents measured at the start of the light period were similar in both high‐light an low‐light treatments. However, by 6 h into the light period, the carbon contents in the high‐light cells were about twofold higher than in the low‐light cells. Dark respiration rates, dark Chl a synthesis rates, and dark cell‐division rates were greater in the high‐light acclimated cells than in the low‐light cells. Thus, there was a greater uncoupling of carbon assimilation from cell division during the day in the high‐light cells, but pigment synthesis and cell division continued in darkness. Cell‐specific, light saturated photosynthesis rates, and chlorophyll a specific lightlimited photosynthesis rates were constant during reciprocal shifts between growth irradiances of 50 and 1200 µmol photons m −2 s −1 . Thus, differences of photosynthesis versus irradiance curves between cells acclimated to high‐light versus low‐light could be accounted for largely in terms of changes in cell chlorophyll a contents. Although the chlorophyll a‐specific initial slope, α chl , was constant, the chlorophyll a‐specific light absorbtion coeffecient, a chl , increased and the maximum quantum efficiency of photosynthesis (φ m ) declined following the shift to high light. The increase of a chl was most likely due to a decreased package effect. The decline of φ m was most likely due to accumulation of xanthophyll cycle pigments. Carbon‐specific, light‐saturated photosynthesis rates were lower in high‐light than in low‐light cells; this observation may indicate that control of light‐saturated photosynthesis shifts from enzymes of the carbon dioxide reduction cycle (Calvin cycle) in low‐light cells to the photosynthetic electron transfer chain in high‐light cells.